GRAVES’ DISEASE WITH NON-FUNCTIONING PITUITARY ADENOMA - Wahinuddin Sulaiman; R. Giritharan; Zakaria Kadir; Cheang Chee Keong (Asian Journal of Medicine & Health Sciences, 2020)
Pituitary adenoma may be associated with hyperthyroidism if there is excess production of thyroid stimulating hormone (TSH). However, the occurrence of Graves’ disease and this slow-growing benign pituitary tumor (1% of functioning adenomas producing TSH) is rare. We report a case of difficult to control Graves’s disease with myopathy diagnosed for the past 1 year. Pituitary adenoma was incidentally found when patient developed Addisonian crisis complicating severe gastroenteritis.